Problems and Optimization Countermeasures in Material Management and Financial Accounting of Wind Power Enterprises - Kang, Yong (Journal of Theory and Practice of Management Science, 2023)
This paper takes the material management and financial accounting of wind power enterprises as the ft point, and discusses the main drawbacks in the material management and financial accounting process of wind power enterprises. At the same time, on this basis, the optimization countermeasures for the drawbacks and problems are explained. It is hoped that the discussion in this paper can help the relevant staff of wind power enterprises to better standardize the management of enterprise materials and improve enterprise capital Effectiveness and safety of production management.